2012
DOI: 10.1111/liv.12049
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of mitochondrial proteins associated with autophagy in biliary epithelial lesions in primary biliary cirrhosis

Abstract: Deregulated autophagy may contribute to the abnormal expression of mitochondrial antigens and may be involved in the autoimmune pathogenesis of bile duct lesions in PBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 51 publications
3
49
0
1
Order By: Relevance
“…While rarefaction of bile ducts is a histopathologic hallmark of the disease, it is under debate whether cholangiocellular damage is the cause or consequence of the autoimmune attack towards bile ducts [2]. However, there is increasing evidence that biliary damage triggers autoimmunity in this disease [23,24]. It therefore seems crucial to better understand and characterize cholangiocellular pathophysiology in order to further unravel the pathogenesis of chronic cholangiopathies.…”
Section: Discussionmentioning
confidence: 99%
“…While rarefaction of bile ducts is a histopathologic hallmark of the disease, it is under debate whether cholangiocellular damage is the cause or consequence of the autoimmune attack towards bile ducts [2]. However, there is increasing evidence that biliary damage triggers autoimmunity in this disease [23,24]. It therefore seems crucial to better understand and characterize cholangiocellular pathophysiology in order to further unravel the pathogenesis of chronic cholangiopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Since mitochondria are a major target of autophagy, we hypothesized that deregulated autophagy of mitochondria may be involved in autoimmune pathogenesis in PBC [24] . We found that the granular expression of PDC-E2 was seen in damaged small bile ducts in PBC ( fig.…”
Section: Autoimmune Process Toward Mitochondrial Antigens and Deregulmentioning
confidence: 99%
“…We found that the granular expression of PDC-E2 was seen in damaged small bile ducts in PBC ( fig. 2 ) [24] . This type of PDC-E2 expression was not seen in other control-diseased liver, such as chronic viral hepatitis [24] .…”
Section: Autoimmune Process Toward Mitochondrial Antigens and Deregulmentioning
confidence: 99%
See 2 more Smart Citations